Multimodal Reduction of Elastic Vibrations in Plate Structure using Super Absorbent Polymer Beads - Takahiro Tomioka; Karen Minamisawa (EPI International Journal of Engineering, 2020)
This paper deals with multimodal reduction of structural elastic vibrations. Super absorbent polymer beads (SAP beads) have been introduced as a simple damping device inspired by the multimodal vibration reduction effect by passengers on railway vehicles. A series of vibration measurement tests using a 1:10 scale model of railway vehicle floor structure (model underframe) was carried out. The SAP beads which are sold commonly as water retention agent were stacked in a container and applied to the model underframe. From the experiments, multimodal vibration reduction effects have been demonstrated. A drastic difference has been observed when water was added together with SAP beads. To investigate the basic mechanism of the damping effect obtained by the experiments, an analytical model, which consists of multiple masses that are supported at an angle to each other, and its simplified model was proposed and numerical studies were conducted. Some specific combinations of the mass, spring, and damping elements in the model could express the experimental results well, and it has been estimated from the numerical results that each SAP layer act as an un-uniform subsystem.